Multiple Intelligences in Learning Musical Dramas for Prospective Primary School Teachers - Okto Wijayanti; Rukiyati Rukiyati (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
Prospective teachers who get the 7th semester of Drama and Dance Education courses must have competence, one of which is that the teacher can present interesting learning for children with a drama approach, as a multidisciplinary knowledge that can be taught using role playing methods that are taught more interesting, fun, meaningful, interactive and rich experience. As a student, you can develop multiple intelligence in this subject. Programmed and scheduled musical drama training systems are indeed interesting, because each student is given the freedom to give assessments, provide reinforcement, support, correct weaknesses, mistakes and even object to the work of other groups with the strengths and points of view of the subjectivity expressed by each. students. As a result, sportsmanship is needed in this regard. Through an empirical qualitative approach, with lesson study-based inductive thinking logic. This study aims to describe the various intelligences that appear in learning dance drama, especially the work practice of dance drama projects (musical dramas), both individually and in groups obtained from the performance appraisal contained in the instrument. Important notes in the discussion found several findings about the application of Multiple Intelligences in learning dance and drama, namely: 1) Tools to achieve success that are more concerned with the process of achieving results, 2) Integrative Learning dance drama combines various intelligences, 3) Learning dance and dance drama becomes full of challenges, and more fun, 4) Care for the individual differences of students so that emotional management is needed, 5) Instructional based learning is firm and clearly measurable, 6) The importance of reflection for further improvement, 7) Clarity of goals, achievement of competence and each student's feedback needs to be done.